Supporting autistic adults with complex communication needs in making their voices heard: examining an adaptation of the Autism Voices framework - Beauchamp, Myriam L. H.; Scorah, Julie; Elsabbagh, Mayada (Frontiers in Human Neuroscience, 2025)
IntroductionAutistic adults with speech, language and/or cognitive challenges are often excluded from research, particularly from studies examining first-person perspectives, as these generally require that participants have strong speech, language, and cognitive skills. The current pilot study extends previous work and examines whether the Autism Voices framework can be adapted for use with a pre-existing interview the Camberwell Assessment of Need for Adults with Developmental and Intellectual Disabilities-Research version (CANDID-R).MethodsEleven young autistic adults with complex communication needs completed the CANDID-R interview using visual supports. These visual supports were provided to assist participants’ comprehension of interview questions and to support them in answering the interview questions. Participants’ caregivers also completed the interview and their answers to specific validation questions were compared to those of their adult children. Additionally, behavioral observations were also completed.ResultsThe findings from this pilot study indicate that our adaptation of the Autism Voices framework was, at least partially successful in supporting participants in answering the interview questions. Additionally, behavioral observations indicate that the visual supports helped participants remain engaged throughout the interview. However, results also indicate that further adaptations, which we discuss, will be required.ConclusionAutistic people with complex communication needs must be included in research about the lived experiences of autistic people. Building on previous work, we show that, with dedication and imagination, equitable and inclusive research is possible.